2005
DOI: 10.1159/000086996
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of an ‘All-Oral’ Regimen of Capecitabine, Idarubicin and Cyclophosphamide for Metastatic Breast Cancer – Safety, Efficacy and Quality of Life

Abstract: Objective: Patients with metastatic breast cancer (MBC) generally have a poor prognosis. Many of these patients have a good performance status. A new all-oral regimen (XIC) was evaluated in a phase II trial. The impact of the regimen on the safety and efficacy of the drug, as well as quality of life (QOL) of the patients was assessed. Patients andMethods:From September 2000 to September 2001, informed consent was obtained from 20 heavily pretreated women with MBC. They were placed on a 6-week cycle regimen com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Therefore, the focus of the present investigation was the evaluation of QoL in patients with metastatic breast cancer during treatment with capecitabine in a routine setting. Data from this study confirmed former clinical investigations on the efficacy of capecitabine in the treatment of metastatic breast cancer [9,10,11] as well as colorectal cancer [12,13]. These investigations unanimously attested a maintained or improved QoL during capecitabine therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the focus of the present investigation was the evaluation of QoL in patients with metastatic breast cancer during treatment with capecitabine in a routine setting. Data from this study confirmed former clinical investigations on the efficacy of capecitabine in the treatment of metastatic breast cancer [9,10,11] as well as colorectal cancer [12,13]. These investigations unanimously attested a maintained or improved QoL during capecitabine therapy.…”
Section: Discussionsupporting
confidence: 88%
“…The clinical interest in oral chemotherapy regimens is evidenced by the recent publication of other studies in this field. One has investigated the combination of idarubicin, 9 cyclophosphamide and capecitabine, and another combined vinorelbine and capaecitabine 10 …”
Section: Discussionmentioning
confidence: 99%
“…All-oral regimens of capecitabine plus oral vinorelbine also show promise [118][119][120][121][122][132][133][134]. Other combinations attracting interest include capecitabine plus oral idarubicin [135], capecitabine plus oral cyclophosphamide [136], capecitabine/ idarubicin/cyclophosphamide triple combination [124], and capecitabine plus tipifarnib [137]. Studies of metronomic therapy using an all-oral combination of cyclophosphamide and methotrexate suggest that this is an effective and minimally toxic approach [128][129][130].…”
Section: All-oral Combinationsmentioning
confidence: 99%